Biomass production and secretion of hydrolytic enzymes are influenced by the structural complexity of the nitrogen source in Fusarium oxysporum and Aspergillus nidulans - Silva, Maybi Cristina Da [UNESP]; Bertolini, Maria Célia [UNESP]; Ernandes, José Roberto [UNESP] (My University, 2001)
The structural complexity of the nitrogen sources strongly affects biomass production and secretion of hydrolytic enzymes in filamentous fungi. Fusarium oxysporum and Aspergillus nidulans were grown in media containing glucose or starch, and supplemented with a nitrogen source varying from a single ammonium salt (ammonium sulfate) to free amino acids (casamino acids), peptides (peptone) and protein (gelatin). In glucose, when the initial pH was adjusted to 5.0, for both microorganisms, higher biomass production occurred upon supplementation with a nitrogen source in the peptide form (peptone and gelatin). With a close to neutrality pH, biomass accumulation was lower only in the presence of the ammonium salt. When grown in starch, biomass accumulation and secretion of hydrolytic enzymes (amylolytic and proteolytic) by Fusarium also depended on the nature of the nitrogen supplement and the pH. When the initial pH was adjusted to 5.0, higher growth and higher amylolytic activities were detected in the media supplemented with peptone, gelatin and casamino acids. However, at pH 7.0, higher biomass accumulation and higher amylolytic activities were observed upon supplementation with peptone or gelatin. Ammonium sulfate and casamino acids induced a lower production of biomass, and a different level of amylolytic enzyme secretion: high in ammonium sulfate and low in casamino acids. Secretion of proteolytic activity was always higher in the media supplemented with peptone and gelatin. Aspergillus, when grown in starch, was not as dependent as Fusarium on the nature of nitrogen source or the pH. The results described in this work indicate that the metabolism of fungi is regulated not only by pH, but also by the level of structural complexity of the nitrogen source in correlation to the carbon source.